Musical Familiarity and Its Effect on Consumer Decision Making - Mahsal Khan, Syazwani; Abdul Hamid, Norsiah; Mohd Rashid, Sabrina (2018)
The purpose of this article is to discuss a study conducted to explore how musical familiarity in advertising can affect decision making of young consumers toward advertised products and services. The method used for the study is the utilization of in-depth interview with experts. The in-depth interview involved ten informants which comprised of academicians, advertising practitioners and musicians. Participants for this approach were chosen based on snowball sampling. This study applies Elaboration Likelihood Model (ELM) to view the process of decision making made by the young consumers. Using thematic analysis there are two themes emerged from this study (i) Repetition of Musical Tone (ii) Music as Remembrance. The finding from this research may provide contribution in two areas which is advertising industry and music industry on producing familiar tone but catchy sounds for advertising perspectives. Hence, this study gives an insight for advertising industry in developing advertisements with suitable musical influence.